Annosum Root Rot of Southern Pines - Tyler Dreaden; Jason Smith (EDIS, 2010)
FOR269, a 3-page illustrated fact sheet by Tyler Dreaden and Jason Smith, describes this damaging forest pathogen that infects a wide range of species, including southern pine, and can cause tree mortality, reduced growth rates, susceptibility to attack by bark beetles, and regeneration failure. Includes references. Published by the UF School of Forest Resources and Conservation, July 2010.